Investigation of Seizure-Susceptibility in a Drosophila melanogaster Model of Human Epilepsy with Optogenetic Stimulation - Saras, Arunesh (Genetics, 2017)
We examined seizure-susceptibility in a Drosophila model of human epilepsy using optogenetic stimulation of ReaChR (red-activatable channelrhodopsin). Photostimulation of the seizure-sensitive mutant para(bss1) causes behavioral paralysis that resembles paralysis caused by mechanical stimulation, in many aspects. Electrophysiology shows that photostimulation evokes abnormal seizure-like neuronal firing in para(bss1) followed by a quiescent period resembling synaptic failure and apparently responsible for paralysis. The pattern of neuronal activity concludes with seizure-like activity just prior to recovery. We tentatively identify the mushroom body as one apparent locus of optogenetic seizure initiation. The α/β lobes may be primarily responsible for mushroom body seizure induction.